Optimizing the physical activity intervention for older adults with mild cognitive impairment: a factorial randomized trial - Shao, Zhanfang; Huang, Jundan; Feng, Hui; Hu, Mingyue (Frontiers in Sports and Active Living, 2024)
Background Physical activity (PA) intervention is one of the most effective interventions to promote cognitive function of older adults with mild cognitive impairment (MCI). However, the level of PA remains low. Based on the two core interventions (X-CircuiT and health education), this study aimed to examine the effect of three implementation strategies (viz., role modeling, goal-setting, and reminding) on the PA level among older adults with MCI using the multiphase optimization strategy (MOST). Methods Participants were randomized into one of eight conditions in a factorial design involving three factors with two levels: (i) role modeling (on vs. off); (ii) goal-setting (on vs. off); and (iii) reminding (on vs. off). The primary outcome was PA level at 12 weeks. The secondary outcomes were cognitive function, self-efficacy, and cost-effectiveness at 12 weeks. The intention-to-treat (ITT) analysis was performed as the main analysis and the per-protocol (PP) analysis as the sensitivity analysis. Results A total of 107 participants were included and randomly assigned into three groups, each receiving different implementation strategies. The results of the multivariate regression analysis showed that the three implementation strategies, namely, reminding (B = 0.31, p < 0.01), role modeling (B = 0.21, p < 0.01), and goal-setting (B = 0.19, p < 0.01), could significantly improve PA level. Specifically, it was found that role modeling (B = 0.68, p = 0.03) could significantly improve cognitive function. There were no significant interactions among the three implementation strategies. Role modeling was the most cost-effective strategy, costing 93.41 RMB for one unit of PA. Conclusions Role modeling was likely to be the best implementation strategy. The value-based and cost-effective PA intervention package could include the core intervention (X-CircuiT and health education) and implementation strategy (role modeling). Clinical Trial Registration https://www.chictr.org.cn, The study was retrospectively registered on 30 June 2022 (ChiCTR2200061693).